1999
DOI: 10.1021/js980221r
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long-Term Stability Studies of Deoxy Hemoglobin and Characterization of Ascorbate-Induced Modifications

Abstract: The reaction of ascorbate with recombinant hemoglobin (rHb1.1) in the presence of differing partial pressures of oxygen was studied. In the presence of 15 000 ppm (1.5%) residual oxygen, ascorbate/oxygen-mediated reactions resulted in an increased rate of autoxidation, modification of the beta-globin, increased oxygen affinity and decreased maximum Hill coefficient. One of the observed modifications to the beta-globin was a 72 Da addition to its N-terminus. Detailed characterization indicates the modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…15 Similarly, subvisible particle counts in a recombinant hemoglobin product documented that particles smaller than 10 μm were approximately two orders of magnitude greater in number than particles larger than 10 μm. 16 As demonstrated by these examples, protein products that contain extremely large numbers of particles smaller than 10 μm might meet the current USP requirement for subvisible particles. If only particles > 10 μm were quantified in a given product, there could be gaps in understanding of important degradation products and in product quality assessment.…”
Section: Critical Gaps In the Analysis And Control Of Subvisible Partmentioning
confidence: 96%
See 1 more Smart Citation
“…15 Similarly, subvisible particle counts in a recombinant hemoglobin product documented that particles smaller than 10 μm were approximately two orders of magnitude greater in number than particles larger than 10 μm. 16 As demonstrated by these examples, protein products that contain extremely large numbers of particles smaller than 10 μm might meet the current USP requirement for subvisible particles. If only particles > 10 μm were quantified in a given product, there could be gaps in understanding of important degradation products and in product quality assessment.…”
Section: Critical Gaps In the Analysis And Control Of Subvisible Partmentioning
confidence: 96%
“…8,15,16 For example, during filling pump operations, it was found that an IgG formed hundreds of thousand of particles per ml in the 1.5–3 μm size range, but less than 1000 particles per ml in the 8–15 μm size range. 8 In a formulation study of a therapeutic cytokine formulated with human serum albumin, more than 90% of subvisible particles were in the 1–2 μm size range, 7–9% were 2–10 μm and less 0.01% were larger than 10 μm.…”
Section: Critical Gaps In the Analysis And Control Of Subvisible Partmentioning
confidence: 99%
“…Otherwise, formulation strategies for mitigating oxidation are somewhat limited. Minimizing exposure to oxygen, by reducing the headspace in the vial, appears to be effective (225,228,231). This is particularly important for Met oxidation, where even less potent oxidants can cause damage.…”
Section: Protection Against Oxidationmentioning
confidence: 99%
“…However, different forums of agitation could potentially generate different species of aggregates both qualitatively and quantitatively. 348 Many proteins easily aggregate during agitation; examples include an antibody, 349 a mAbIgG1, 348,350 an IgG4, 351 the variable domain of an IgG light chain (114 aa), 57 IL -2 mutein, 223 Albutropin, 226 rFXIII, 346 hGH, 228,230,251 and insulin, 23,352 deoxy hemoglobin, 353 and α -synuclein (natively unfolded protein). 163 Surfactants are most commonly used and are generally effective in reducing shaking/shearinginduced protein aggregation, such as Tweens for IL -2 mutein, 223 factor XIII 346 or rhGH, 261 Pluronic F68, or Brij 35 for rhGH.…”
Section: Agitationmentioning
confidence: 99%